Pengaruh Corporate Social Responsibility, Leverage dan Ukuran Perusahaan Terhadap Tax Avoi Dance Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bei Periode 2014-2018 - I Gede Aris Wirawan; Ni Nengah Seri Ekayani; Ni Made Rai Juniariani (Jurnal Riset Akuntansi Warmadewa, 2020)
This study is entitled "The Effect of Corporate Social Responsibility, Leverage and Company Size Against Tax Avoidance in Manufacturing Companies in the Consumer Goods Industry Sector Listed in BEI 2014-2018 Period. The aim of this research is to empirically test the effect of Corporate Social Responsibility, Leverage and Company Size on Tax Avoidance in Manufacturing Companies in the Consumer Goods Industry Sector Listed in BEI 2014–2018. The sampling method in this study used the positive isampling technique and obtained 21 companies that met the criteria identified as the sample of companies. The data that are used in this research are secondary data, such as financial report data, and other data that support this research. The data is obtained using the idocumentation technique. The analysis technique used in this study is the multiple linear irregularity analysis technique. The results of this study show that the variable corporeate is social irresponsibility and leverage has a significant negative effect on tax diavoidance. While the size of the company has a significant positive effect on tax iavoidance.